A Comparison of Determinants of Bank Profitability in the UK and China - Wang, Meng (2022)
This article focuses on the mechanisms of each influencing element on commercial bank profitability in China and the United Kingdom, as well as the important factors impacting commercial bank profitability in China and the United Kingdom. To begin, it is a research project that examines the influential aspects as well as the technique. Second, a panel data set was created using financial data from the top 50 commercial banks in China and the United Kingdom from 2016 to 2020, as well as macroeconomic data. After that, Stata software was used to create a fixed effects regression model to examine the specific association between each influencing element and commercial bank profitability. Finally, the following results were drawn: bank size, asset quality, GDP growth, inflation rate, and money supply growth all have substantial effects on UK commercial bank profitability. Apart from the two variables of capital quality and inflation, other bank-specific and macroeconomic causes have a major impact on the level of bank profitability when examined from the perspective of Chinese commercial banks.